Validasi Kriteria Pemilihan Karyawan Terbaik menggunakan Multi Criteria Decision Making (MCDM) (Studi Kasus Pada PT AIND) - Sulistyanto, Tri Hadi; Mistina, Rahayu Septyaning; Muslimin, Cecep Jaenal; Heryani, Yeni (Fakultas Ekonomi dan Bisnis Universitas Islam DR KH EZ Mutaqien, 2024)
This research aims to examine and provide validation for the best employee selection process conducted by PT AIND. The selection of the best employees that has been done so far is based on the weight of the criteria determined where the weight of each criterion is not yet known as the basis for its determination, thus creating a risk of selecting unsuitable candidates. The AHP (Analytical Hierarchy Process) method is based on a hierarchical structure, making it more focused on each criterion and transparent in determining the weight of each criterion. PT AIND can use this method in the process of selecting the best employees more transparently and rationally. The results of this study obtained the weight of each criterion which is used to determine the best employees in the company based on pairwise comparisons of each criterion more rationally and reliably. Other criteria (sub-criteria) can be added to the best employee selection process, and each criterion's weight can be reassigned using the AHP method with pairwise comparisons of the currently used criteria.